2020
DOI: 10.1016/j.applanim.2020.105103
|View full text |Cite
|
Sign up to set email alerts
|

Pigs with but not without access to pieces of recently harvested wood show reduced pen-mate manipulation after a provision of feed and straw

Abstract: In barren environments of commercial farms, pig often redirect their rooting and chewing behaviours at other pigs, which can lead to tail biting. When materials such as straw are provided, the quantity is usually too small to have an effect. The aim of this study was to test whether small provisions of straw and species-relevant point-source objects would have an additive effect in reducing pen-mate manipulation. The animals were 167 gilts with undocked tails on a commercial farm in Finland, housed in 12-m2 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In the present study, enrichment items (pine and scented wood) could significantly reduce the stereotypical behavior and physiological stress in sows, but with no significant difference between the two enrichment items in their effects. This is consistent with previous reports that fresh wood could reduce tail biting, ear biting and manipulation behavior, and the use of natural flavors in objects suitable for nibbling can encourage weaned piglets to maintain a longer strong interest [ 8 , 31 ]. Based on the frequency and duration of enrichment items manipulation by pregnant sows, there is no difference in the degree of interest in the two enrichment items (pine and scented wood) for the sows in the third trimester of pregnancy in the confinement stalls, suggesting that artificial scented wood has the same effect of pine wood.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, enrichment items (pine and scented wood) could significantly reduce the stereotypical behavior and physiological stress in sows, but with no significant difference between the two enrichment items in their effects. This is consistent with previous reports that fresh wood could reduce tail biting, ear biting and manipulation behavior, and the use of natural flavors in objects suitable for nibbling can encourage weaned piglets to maintain a longer strong interest [ 8 , 31 ]. Based on the frequency and duration of enrichment items manipulation by pregnant sows, there is no difference in the degree of interest in the two enrichment items (pine and scented wood) for the sows in the third trimester of pregnancy in the confinement stalls, suggesting that artificial scented wood has the same effect of pine wood.…”
Section: Discussionsupporting
confidence: 92%
“…A review of the literature indicated that possible issues that may be associated with some environmental enrichments are waste management problems, biosecurity concerns, sourcing the materials or possible composting problems [13]. Managers of swine facilities with concrete slatted floors and liquid manure systems are concerned that straw will clog their systems [14]. The amount of straw required to reduce tail biting may cause waste management problems.…”
Section: Possible Barriers To Implementation Of Environmental Enrichmentmentioning
confidence: 99%
“…To avoid problems with waste management, pigs on partially slatted floors can be given up to 20 g of straw per pig each day. Unfortunately, this small amount of straw may not be effective for reducing tail biting [14]. One study showed that the amount of straw could be reduced by providing birch wood pieces [14].…”
Section: Effective Enrichments For Pigsmentioning
confidence: 99%
See 1 more Smart Citation
“…In T3, the occurrence of oral manipulation of pen mates was higher in pigs that had access to balls attached to chains than pigs that had access to any other enrichment material. Previous studies found that enrichment material that facilitates rooting, such as straw or peat, is of high interest and reduces manipulation behaviour directed towards other pigs (Oostindjer et al, 2011b;Telkänranta and Valros, 2020;Vanheukelom et al, 2011). Balls on chains provide relatively little opportunity for rooting behaviour (Day et al, 2002), which may explain the higher level of oral manipulation of pen mates when pigs only had access to this enrichment.…”
Section: Discussionmentioning
confidence: 99%